A. McMicken, City Attorney, The Revised Ordinances of the City of Rawlins, Carbon County, Wyoming, at 131-32, Article VII, Carrying Firearms and Lethal Weapons, § 1 (1893) - (:unkn) unknown (General Publisher, 1893)
Prohibited a person from possessing or carrying a pistol, revolver, knife, slungshot, bludgeon or other lethal weapon. Punishable by fine up to $100 or imprisonment up to 30 days.
--
Keywords: POSSESSION